1999
DOI: 10.1182/blood.v93.9.3064.409k07_3064_3073
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Neovascularization, Plasma Cell Angiogenic Potential, and Matrix Metalloproteinase-2 Secretion Parallel Progression of Human Multiple Myeloma

Abstract: To assess whether the progression of plasma cell tumors is accompanied by angiogenesis and secretion of matrix-degrading enzymes, bone marrow biopsy specimens from 20 patients with monoclonal gammopathy of undetermined significance (MGUS), 18 patients with nonactive multiple myeloma (MM), and 26 patients with active MM were evaluated for their angiogenic potential and matrix-metalloproteinase (MMP) production. A fivefold increase of the factor VIII+microvessel area was measured by a planimetric method of point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(105 citation statements)
references
References 34 publications
5
92
0
8
Order By: Relevance
“…Multiple myeloma cell growth is associated with angiogenesis (44,45). As noted earlier, ANPEP expression/ activity is associated with malignant phenotype, including angiogenesis (46); and importantly, mel-flufen is ANPEP-activated prodrug of melphalan.…”
Section: Effect Of Mel-flufen On Migration Of Multiple Myeloma Cells mentioning
confidence: 87%
See 1 more Smart Citation
“…Multiple myeloma cell growth is associated with angiogenesis (44,45). As noted earlier, ANPEP expression/ activity is associated with malignant phenotype, including angiogenesis (46); and importantly, mel-flufen is ANPEP-activated prodrug of melphalan.…”
Section: Effect Of Mel-flufen On Migration Of Multiple Myeloma Cells mentioning
confidence: 87%
“…We examined the effect of mel-flufen on multiple myeloma cell migration and angiogenesis using Transwell insert systems and in vitro tubule formation assays. VEGF is elevated in the multiple myeloma bone marrow microenvironment, and prior studies showed that VEGF triggers growth, migration, and angiogenesis in multiple myeloma (44,45,47). We first examined whether mel-flufen affects VEGFinduced multiple myeloma cell migration.…”
Section: Effect Of Mel-flufen On Migration Of Multiple Myeloma Cells mentioning
confidence: 99%
“…In keeping with results obtained in solid tumours, our results qualify S-VEGF as a marker suitable for predicting the clinical outcome of disease also in haemopoietic neoplasias such as CLL. As a matter of fact in MM an increased angiogenesis was implicated in the mechanisms of progression from MGUS or non-active MM to active MM (Vacca et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these ®ndings suggesting a central role of angiogenesis in the mechanisms of progression of many solid tumours, little is known regarding angiogenesis in response to haematological malignancies. Increased micovessel density has been reported in BM of active multiple myeloma (MM) in comparison with nonactive MM and monoclonal gammopathy of undetermined signi®cance (MGUS) patients (Vacca et al, 1999).…”
mentioning
confidence: 99%
“…Specifically, increased microvessel density (MVD) in MM patient BM specimens parallels disease progression and correlates with poor prognosis (Vacca et al, 1999), and BM MVD at diagnosis is an important prognostic factor for survival of patients who undergo autologous transplantation as frontline therapy. Bone marrow angiogenesis is partly sustained by VEGF, basic fibroblast growth factor (bFGF), and matrix metalloproteinases (MMPs) secreted by MM cells (Vacca et al, 1999). Conversely, BMECs secrete growth factors, including VEGF and bFGF, promoting MM cell growth in the BM milieu ( Fig 1).…”
Section: Bone Marrow Endothelial Cellsmentioning
confidence: 99%